The Influence Of Brand Awareness, Content Marketing, And Product Innovation On Purchase Decisions For Mixue Ice Cream Products In The West Circle Of Bengkulu City - Silvia Septiani; Eti Arini (Journal of Indonesian Management, 2024)
This study aims to determine the influence of Brand Awareness, Content Marketing and Product Innovation on Purchase Decisions for Mixue Ice Cream Products in the West Circle of Bengkulu City for mixue consumers in the West Circle of Bengkulu City. This type of research is a quantitative descriptive type of research, the object of this research is Mixue Consumers in the West Circle of Bengkulu City. The sampling method is an accidental sampling technique. The number of respondents in this study was 100 respondents. The data collection method is using questionnaires. The data analysis technique uses Multiple Linear Regression Analysis Test and Hypothesis Testing, namely the t test and f test. The results of this research can be concluded that Brand Awareness has a positive and significant effect on Mixue product purchasing decisions. Content Marketing has a positive and significant influence on Mixue product purchasing decisions. Product Innovation has a positive and significant effect on Mixue product purchasing decisions. This is proven by fcount ≥ ftable (121,608 ≥ 2.70) with a significance of 0.000 ≤ 0.050. The coefficient of determination (R Square) is 0.755. This shows that the influence of the Brand Awareness (X1), Content Markting (X2) and Product Innovation (X3) variables on the Purchasing Decision Variable (Y) is 0.755 or 75.5% for west ring mixue consumers while 0.245 or 24.5% is determined by other factors which were not included in this study.